Towards Global Volunteer Monitoring of Odonate Abundance. (16th September 2020) - Bried, Jason; Ries, Leslie; Smith, Brenda; Patten, Michael; Abbott, John; Ball-Damerow, Joan; Cannings, Robert; Cordero-Rivera, Adolfo; Córdoba-Aguilar, Alex; De Marco, Paulo; Dijkstra, Klaas-Douwe; Dolný, Aleš; et al.
Abstract: Insects are reportedly experiencing widespread declines, but we generally have sparse data on their abundance. Correcting this shortfall will take more effort than professional entomologists alone can manage. Volunteer nature enthusiasts can greatly help to monitor the abundance of dragonflies and damselflies (Odonata), iconic freshwater sentinels and one of the few nonpollinator insect groups appreciated by the public and amenable to citizen science. Although counting individual odonates is common in some locations, current data will not enable a global perspective on odonate abundance patterns and trends. Borrowing insight from butterfly monitoring efforts, we outline basic plans for a global volunteer network to count odonates, including organizational structure, advertising and recruiting, and data collection, submission, and synthesis. We hope our proposal serves as a catalyst for richer coordinated efforts to understand population trends of odonates and other insects in the Anthropocene.